IMPACT OF FLOODING ON ELEMENTARY STUDENTS’ PERFORMANCE IN SOUTH PUNJAB - Aniq ur Rehman; Dr. Ismat Bani (International Journal of Contemporary Issues in Social Sciences, 2024)
Floods are a serious danger to educational systems, particularly in regions like South Punjab that are powerless against them. This review takes a gander at how South Punjabi rudimentary schoolchildren perform when there is flooding, with a specific accentuation on the interruptions to their schooling, the mental repercussions, and the financial implications. Reviews, meetings, and center gatherings were utilized to assemble data, which uncovered the range of troubles that networks, teachers, and understudies stand up to. The primary impacts of flooding, as indicated by the discoveries, are broadened school terminations, infrastructural harm, and mental inconvenience among understudies. The exploration features the need of comprehensive measures to reduce these results and advance flexibility in locales vulnerable to flooding.